PENGELOLAAN SUMBER DAYA AIR BERBASIS MASYARAKAT DALAM PEMENUHAN KEBUTUHAN RUMAH TANGGA DI DESA SEJAHTERA KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Purwanto, Herry (JURNAL BORNEO AKCAYA, 2016)
Community based management appropriate in the management of water resources, due to the public as consumers once served as the manager would better understand the needs of the community itself. Community-based management in the District Sukadana Prosperous Village District of North Kayong will work properly if there is a willingness of the community to participate. Research on water has been more focused on biosifik water alone, in this study the researchers focused on human ie on community participation. This research uses descriptive method with data analysis using inductive logic absrtaktif which starts from the particular to the general, conceptualizing and categorizing. Description developed on the basis of events obtained when the field work took place. Therefore, the data collection and data analysis becomes an integral, both take place simultaneously or simultaneously. This study found the management of water resources in meeting the needs of households in the District Sukadana Prosperous Village District of North Kayong very good. However, there are several factors that influence community participation in water resource management, community-based nature of these factors can support a successful management, but there are also nature can affect the success. Age, sex, education, occupation and income, is usually mentioned as internal factors or from within the community, although no significant effect. From this study showed that the management of water resources in the District Prosperous Village Sukadana can be said to be good. The level of public participation is an indicator in assessing the level of community based management. There is a willingness from the people involved in mutual cooperation, willingness to pay dues, willing to participate in a meeting or a meeting to discuss the management of water resources. Other internal factors affecting partisipasi society is the type of work and sex. Those who work as civil servants or private sector and farmers have different times, so the time will determine the willingness of mutual cooperation and meetings. Of sex between men, women and children, have levels and different forms of participation. Finally, researchers can group the hypothesis of this study is "Management and utilization of natural resources (in this study is the water resources) are related and have a relevant correlation with the quality of Human Resources in the vicinity